Why is Mini-Mental state examination performance correlated with estimated premorbid cognitive ability?. Issue 12 (5th July 2016) - Dykiert, D.; Der, G.; Starr, J. M.; Deary, I. J.
Abstract : Background: Tests requiring the pronunciation of irregular words are used to estimate premorbid cognitive ability in patients with clinical diagnoses, and prior cognitive ability in normal ageing. However, scores on these word-reading tests correlate with scores on the Mini-Mental State Examination (MMSE), a widely used screening test for possible cognitive pathology. This study aimed to test whether the word-reading tests' correlations with MMSE scores in healthy older people are explained by childhood IQ or education. Method: Wechsler Test of Adult Reading (WTAR), National Adult Reading Test (NART), MMSE scores and information about education were obtained from 1024 70-year-olds, for whom childhood intelligence test scores were available. Results: WTAR and NART were positively correlated with the MMSE ( r ≈ 0.40, p < 0.001). The shared variance of WTAR and NART with MMSE was significantly attenuated by 70% after controlling for childhood intelligence test scores. Education explained little additional variance in the association between the reading tests and the MMSE. Conclusions: MMSE, which is often used to index cognitive impairment, is associated with prior cognitive ability. MMSE score is related to scores on WTAR and NART largely due to their shared association with prior ability. Obtained MMSE scores should be interpreted in the context of prior ability (or WTAR/NART score as its proxy).